ISHMATUL ANBIYÂ’: (Sebuah Proteksi Ketuhanan untuk Para Nabi) - Iman, Sunardi Bashri (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Infallibility is established for the prophets and apostles, as proven by the texts of the Koran and strong scientific reasoning. Infallibility is God's protection against them from falling into sin, immorality, transgression, and committing evil and forbidden acts after being sent, according to the agreement of pious researchers, and before being sent, according to evidence. How could our Lord command men to follow them, imitate them, and follow their ways if they were not examples of perfection, examples of virtue, nobility, and holiness? If infallibility were not one of their characteristics, then we would not be obliged to follow them in all actions and deeds. As for the texts of the Shari'a which indicate the existence of sins and violations committed by some of the prophets -may Allah have mercy on them-, then this can be understood as follows: Firstly, this is not a sin, but rather an action that is contrary to the first, or an error in judgment. Assuming that it was a transgression or sin, then it must have occurred before prophethood.